Sustainable Tourism Development Through Ecotourism Development in Paccekke Village - Ernawati S. Kaseng (Jurnal Ekonomi dan Riset Pembangunan, 2023)
Currently, the development of the tourism sector is very massively developed by the government. This is triggered by the increasing need for recreation and adventure in new areas that present natural beauty where they have never been to and interact with the local community. This research article aims to describe the potential of ecotourism and the supporting and inhibiting factors for the development of ecotourism in Paccekke Village. This research article uses descriptive-qualitative methods. The research informant was chosen deliberately. Primary data is obtained through interviews and observations while secondary data is obtained through data from research-related agencies. Data analysis using qualitative descriptive analysis. The results of the research study show that the ecotourism potential of Paccekke Village is not only the beauty of natural beauty that is still natural and clean natural bathing but there is also a Paccekke Monument which has historical value. Then it also has artificial tourism potential in the form of Embung Paccekke and Agro tourism potential as well as the potential for cultural events. The supporting factors are, the natural and cultural potential of the village; sustainable natural conditions; positive attitude of the community towards tourism and mutual aid culture; the existence of cultural events; and the commitment of village stakeholders. Inhibiting factors, namely, limited facilities and infrastructure; weak planning in the field of tourism; extreme accessibility; weak network and internet; and low awareness and ability of the community to manage tourism potential.